2020
DOI: 10.3389/fimmu.2020.01109
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T Cells Hit the Tumor Microenvironment: Strategies to Overcome Tumor Escape

Abstract: Chimeric antigen receptor (CAR) T cell therapies have demonstrated remarkable efficacy for the treatment of hematological malignancies. However, in patients with solid tumors, objective responses to CART cell therapy remain sporadic and transient. A major obstacle for CART cells is the intrinsic ability of tumors to evade immune responses. Advanced solid tumors are largely composed of desmoplastic stroma and immunosuppressive modulators, and characterized by aberrant cell proliferation and vascularization, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
173
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(192 citation statements)
references
References 234 publications
0
173
0
2
Order By: Relevance
“…Physical barriers such as the stiff tumor stroma further hinder the infiltration of T cells in the tumor. 6,8,87 Some in vivo studies have shown that following adoptive transfer, allogeneic Vγ9Vδ2 T cells can reach, infiltrate tumor sites, and display strong anti-tumor activities. 88,89 However, chemokine receptors that are essential for the recruitment of lymphocytes to tumors (eg, CXCR1-3) 90 hinder T cell trafficking, using CAR designed to specifically target VEGFR2 that plays vital roles in tumor angiogenesis and growth 94 or the fibroblast activation protein that is expressed at the surface of cancer-associated stromal cells.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…Physical barriers such as the stiff tumor stroma further hinder the infiltration of T cells in the tumor. 6,8,87 Some in vivo studies have shown that following adoptive transfer, allogeneic Vγ9Vδ2 T cells can reach, infiltrate tumor sites, and display strong anti-tumor activities. 88,89 However, chemokine receptors that are essential for the recruitment of lymphocytes to tumors (eg, CXCR1-3) 90 hinder T cell trafficking, using CAR designed to specifically target VEGFR2 that plays vital roles in tumor angiogenesis and growth 94 or the fibroblast activation protein that is expressed at the surface of cancer-associated stromal cells.…”
Section: F I G U R Ementioning
confidence: 99%
“…Adoptively transferred T cells can be engineered to improve their direct anti-tumor function by increasing their recognition of the tumors, their trafficking to the tumor site, and their resistance to the suppressing effect of the tumor microenvironment. [5][6][7][8] Moreover, adoptively transferred T cells can be engineered as "armored" T cells, to harness the endogenous immune system in mounting an effective anti-tumor response, generally through local delivery of molecules within the tumor. 9 In this review, we present the current T cell-based ACT strategies, their limitations, and the solutions currently proposed to circumvent these limitations through genetic engineering of adoptively transferred T cells.…”
mentioning
confidence: 99%
“…Likewise, the procession of CD62L, a standard marker of memory cells, in CARs population is more effective against both hematological malignancy and solid tumors, and promoted longer persistence of peripheral NKT and T cells [82][83][84]. Because of timing in infiltration into the tumor site, recognizing the tumor antigen, and performing their function, the memory subtype of CAR T cells is exigency [85]. The selection of T cell subtype population during CAR production or before administration to patients is recommended for improving the efficacy of CARs T cell against neuroblastoma.…”
Section: T Lymphocytementioning
confidence: 99%
“…However, CAR-T cell therapy has not yet had similar results in solid tumors [8][9][10]. Solid tumors have a more complex immunosuppressive microenvironment and there are many immunosuppressive cells and cytokines which inhibit the activation and survival of CAR-T cells within the tumor [11,12]. The dense extracellular matrix (ECM) also prevents CAR-T cells from in ltrating into solid tumors and can affect CAR-T cell activity [13,14].…”
Section: Introductionmentioning
confidence: 99%